The Social Acceptance of Carbon Dioxide Utilisation: A Review and Research Agenda - Jones, Christopher R.; Olfe-Kräutlein, Barbara; Naims, Henriette; Armstrong, Katy (Frontiers in Energy Research, 2017)
CO2 utilisation technologies—also called carbon dioxide utilisation (CDU) and carbon capture and utilisation (CCU)—convert CO2via physical, chemical, or biological processes into carbon-based products. CO2 utilisation technologies are viewed as a means of helping to address climate change and broadening the raw material base for commodities that can be sold to generate economic revenue. However, while technical research and development into the feasibility of CO2 utilisation options are accelerating rapidly; at present, there has been limited research into the social acceptance of the technology and CO2-derived products. This review article outlines and explores three key dimensions of social acceptance (i.e., socio-political, market, and community acceptance) pertaining to innovation within CO2 utilisation. The article highlights the importance of considering issues of social acceptance as an aspect of the research, development, demonstration, and deployment process for CO2 utilisation and explores how key stakeholders operating on each dimension might affect the innovation pathways, investment, and siting decisions relating to CO2 utilisation facilities and CO2-derived products. Beyond providing a state-of-the-art review of current research into the social acceptance of CO2 utilisation, this article also outlines an agenda for future research in the field.